ENGLISH LANGUAGE TEACHING IN INDONESIA - Selmina Rumawak (International Journal of Social Science, 2024)
This paper reports on the English Language Teaching (ELT) in Indonesia and the significance of a proposed approach to the ELT, that is, World Englishes. Library research was conducted to answer principal questions regarding “which prestigious variety should be used, the local English teacher (non-native English teacher) and inner-circle teacher debate (native English teacher), and impact of English affecting local languages. The report concludes with recommendations on how to deal with the three issues”. The first recommendation is to incorporate World Englishes teaching method into ELT in educational institutions nationwide hence provide first-hand experience of varieties of Englishes used in other countries. Secondly, it was suggested that it is more efficient to have both native and non-native English Teachers to teach at a language institution. Lastly, as English travels worldwide it may affect heritage languages thus Jenkins (2015) proposes, students should be made aware of their native languages as their identities and function it together with English (Jenkins, 2015, p. 176). Ultimately, bilingualism is essential in order to employ English as the international language but not forgetting to maintaining local languages as students’ important cultural asset